NO-STRESS METHODS FOR ASSESING READING COMPREHENSION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
This article explores a paradigm shift toward no-stress methods for assessing reading comprehension. We will move beyond the limitations of traditional exams to discover authentic, engaging, and low-pressure techniques that provide richer, more meaningful insights into what a student truly grasps and connects with. From interactive conversations and creative projects to observation and digital tools, these methods prioritize the joy of understanding over the fear of evaluation.